Discovery of Novel Viruses Associated With the Invasive Cane Toad (Rhinella marina) in Its Native and Introduced Ranges - Russo, Alice G.; Harding, Emma F.; Yan, Grace J. H.; Selechnik, Daniel; Ducatez, Simon; DeVore, Jayna L.; Zhou, Jia; Sarma, Roshmi R.; Lee, Yin Peng; Richardson, Mark F.; Shine, Richard; Rollins, Lee A.; et al. (Frontiers in Microbiology, 2021)
Cane toads (Rhinella marina) are notoriously successful invaders: from 101 individuals brought to Australia in 1935, poisonous toads now cover an area >1.2 million km2 with adverse effects on native fauna. Despite extensive research on the role of macroparasites in cane toad invasion, viral research is lagging. We compared viral prevalence and diversity between toads in their native range (French Guiana, n=25) and two introduced ranges: Australia (n=151) and Hawai’i (n=10) with a metatranscriptomic and metagenomic approach combined with PCR screening. Australian toads are infected almost exclusively by only one of seven viruses detected globally. Rhimavirus-A (Picornaviridae) exhibited low genetic diversity and actively infected 9% of sampled Australian toads extending across ~2,000 km of Northern Australia and up to the current invasion front. In native range cane toads, we identified multiple phylogenetically distinct viruses (Iridoviridae, Picornaviridae, Papillomaviridae, Nackedna-like virus). No viruses were detected in both ranges, suggesting that Australian cane toads have largely escaped the viral infection experienced by their native range counterparts. The novel native range viruses described here are potential biocontrol agents, as Australian toads likely lack prior immunological exposure to these viruses. Overall, our evidence suggests that there may be differences between viruses infecting cane toads in their native versus introduced ranges, which lays the groundwork for further studies on how these viruses have influenced the toads’ invasion history.